2012
DOI: 10.1111/j.1464-5491.2011.03565.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased peripheral blood mitochondrial DNA content is related to HbA1c, fasting plasma glucose level and age of onset in Type 2 diabetes mellitus

Abstract: Our results demonstrate that lower peripheral blood mtDNA content is associated with Type 2 diabetes in Chinese individuals, and HbA(1c), fasting plasma glucose and age of onset are the major factors affecting the mtDNA content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
3
46
3
1
Order By: Relevance
“…In this cross-sectional study, we have used a stepwise multiple regression analysis, adjusting for potential confounders such as age,15) BMI,16) and various cardio-metabolic parameters,1718) to show that postmenopausal women who partake in regular exercise have a significantly higher leukocyte mtDNA copy number than postmenopausal women who do not exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cross-sectional study, we have used a stepwise multiple regression analysis, adjusting for potential confounders such as age,15) BMI,16) and various cardio-metabolic parameters,1718) to show that postmenopausal women who partake in regular exercise have a significantly higher leukocyte mtDNA copy number than postmenopausal women who do not exercise.…”
Section: Discussionmentioning
confidence: 99%
“…An independent association between leukocyte mtDNA copy number and exercise was confirmed using a stepwise multiple linear regression model with a significance threshold of 0.15. Potential confounding variables were defined as those that were significantly associated (P<0.1) with leukocyte mtDNA copy number using Pearson's correlation analysis, either in this study (triglyceride, WHR, waist circumference, and homocysteine level), or in previously reported studies (age,15) BMI,16) systolic and diastolic blood pressure, HOMA-IR, and levels of triglyceride and HDL cholesterol1718)). Multicollinearity between independent variables was evaluated using Pearson's correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…An African-American study demonstrated epigenetic factors similar to psychological stress and social context that are correlated with swelling and infection in heart diseases and strokes [5]. Previous studies validated the contribution of epigenomics in the therapeutics of breast cancer [6] in which it was observed that several dietary chemo-preventive agents (retinoids/Vitamin A, green tea, Vitamin D, etc.) acted on the miRNA signaling pathways, so as to obstruct the uncontrolled metabolic mechanisms of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we added baseline eGFR to Models 3 and 4. Because lower mtDNA copy number measured from peripheral blood has been associated with diabetes, one of the strongest risk factors of incident CKD, 42,43 we tested for the interaction between mtDNA copy number and prevalent diabetes on the basis of Model 4. We also conducted sensitivity analyses on the basis of Model 4.…”
Section: Statistical Analysesmentioning
confidence: 99%